Das Arcadas à "SanFran" "A velha e sempre nova Academia ou, a Velha e sempre velha Academia?" - Gaspar, Raisa Yasmin Ranzani [UNIFESP] (2019)
This paper aims to investigate the mechanisms through which the Largo São Francisco Law School is produced and reproduced as a reference in an elite higher education institution. In this sense, the central focus is on the effects produced by this educational establishment on the life trajectory of its members. To this end, this analysis will review the process of institutionalization of legal courses in Brazil and the legal professions, in order to verify how the hierarchy between higher education diplomas in law was established. Secondly, we will evaluate the peculiarities of the Largo São Francisco Law School in maintaining its members' sense of monopoly and nobility, through the application of questionnaires to the students of this institution, which will draw an overview of the social recruitment of these students. . Finally, it will be examined the trajectory of its faculty from the survey of Lattes curricula of these agents. The statements, obtained through interviews with these teachers, aim to apprehend the effects produced by São Francisco in the life trajectory of these agents from their own impressions. Based on this, the investigation seeks to trace the internal cleavages of the USP Faculty of Law, through this diversity of profiles, as a mechanism for identifying the careers patterns of their graduates, as well as the resources used to do so.